Improvement of Negative Psychological Stress Response in Elderly Patients With Femoral Neck Fracture by Integrated High-Quality Nursing Model of Medical Care - Li, Qun; Wang, Yin; Shen, Xiang (Frontiers in Surgery, 2022)
Objective: To explore the nursing effect and negative psychological stress response of elderly patients with femoral neck fracture by applying the high-quality nursing mode of medical care. Methods: 130 elderly patients with femoral neck fractures hospitalized in our hospital from January 2020 to June 2021 were randomly divided into control group and observation group, with 65 patients in each group. The control group adopted the conventional nursing mode, while the observation group adopted the high-quality nursing mode of medical care. The observation indexes selected in this study are nursing satisfaction, hip flexion activity on the 1st, 15st and 30st day after operation, the time when the affected limb was lifted off the bed actively, and the anxiety and depression of patients. Results: On the 1st, 15st and 30st day after operation, there were statistically significant differences between the two groups in hip flexion activity and the time when the affected limb was lifted off the bed (P<0.05). Nursing satisfaction of observation group was 95.38%, which was statistically significant compared with 80.00% of control group (P<0.05). After treatment, SDS and SAS scores in observation group were lower than those in control group (P<0.05). Conclusion: The high-quality nursing model of medical care can effectively promote the rehabilitation of elderly patients with femoral neck fracture, reduce the negative psychological stress reaction of patients and improve nursing satisfaction, which has important application value and guiding significance for the nursing of patients with femoral neck fracture.